(untitled) (Journal of Oriental Studies, 2016)
Abu Mansur al-Maturidi is a founder of sunni Islam style Maturidi kalam school making a great contribution to Islamic science to flourish. His major book is a commentary to Qu’ran, being basis of Islam. In his book he addressed basic iman related issues which led to division of Muslims then and now, as well as the Shariat issues, in line with Qu’ranic verses. Imam Maturidi spent all his life studying and propagating Qu’ranic teachings, thanks to this he left Kitab at-Tawilat behind him which is a priceless book of the Islamic scientific heritage, respected now and then, being an example for “dirayat” style commenting.